KEEFEKTIFAN MODEL SOMATIC, AUDITORY, INTELLECTUALLY, VISUALIZATION PADA MATA PELAJARAN IPA (Jurnal Kreatif : Jurnal Kependidikan Dasar, 2016)
The purpose of this research is was to test the effectiveness of somatic, auditory, visualization, intellectually model on science 4 grade class at elementary school in gatot subroto cluster distric Semarang. This research used an experimental method with a research design that is nonequivalent control group design. The population in this research is student of 4 grade class at elementary school in gatot subroto cluster distric Semarang. The sampling technique is using cluster random sampling. Total sample in this research is 129 students. Data collection technique is using testing and observation. Analyzed using statistical t-test. The average value of the experimental group is 86.25 and the average value of the control group is 74.38. Therefore, it can be concluded that the average learning outcomes of students who were taught using learning model SAVI more effective than those taught using cooperative learning. The analysis of product moment, there is a relationship between learning outcomes and student activity using SAVI models for science instructional Elementary School fourth grade students in Gugus Gatot Subroto. The conclusion of research was SAVI model is effectiveness used on science instructional 4 grade class at elementary school in gatot subroto cluster distric Semarang.